Necrotising fungal scleritis with full-thickness scleral melt and circumferential progression: a novel debridement approach - Karkhur, Samendra (BMJ Case Rep, 2020)
A 44-year-old Asian Indian woman presented with a history of pain and redness in the left eye for 3 weeks. Scleral congestion with a nodular swelling was present inferotemporally. Raised C reactive protein and positive antinuclear and perinuclear antineutrophil cytoplasmic antibodies suggested autoimmune scleritis. The patient was therefore managed with corticosteroids. Nevertheless, the development of severe pain associated with a scleral abscess led to a revised diagnosis of infectious scleritis. Corticosteroids therapy was halted and urgent debridement was performed. Microbiology confirmed fungal scleritis due to Coprinopsis cinerea. Multiple full-thickness circumferential debridements with antifungal therapy resulted in satisfactory anatomical and visual outcomes. This case presented a unique challenge, since laboratory results were misleading, and corticosteroids resulted in a fulminant clinical course. Therefore, aggressive circumferential debridement was performed to achieve the elimination of a rare fungal aetiology of scleritis, which has not been reported previously to cause human infection.